An international randomised trial of celecoxib versus celecoxib plus difluoromethylornithine in patients with familial adenomatous polyposis. Issue 2 (19th March 2015) - Lynch, Patrick M; Burke, Carol A; Phillips, Robin; Morris, Jeffrey S; Slack, Rebecca; Wang, Xuemei; Liu, Jun; Patterson, Sherri; Sinicrope, Frank A; Rodriguez-Bigas, Miguel A; Half, Elizabeth; Bulow, Steffen; et al.
Abstract : Background and aim: Although Non-steroidal anti-inflammatory drugs reduce colorectal adenoma burden in familial adenomatous polyposis (FAP), the utility of combining chemopreventive agents in FAP is not known. We conducted a randomised trial of celecoxib (CXB) versus CXB+diflouromethylornithine (DFMO) to determine the synergistic effect, if any. Methods: The primary endpoint was % change in adenoma count in a defined field. Secondary endpoints were adenoma burden (weighted by adenoma diameter) and video review of entire colon/rectal segments. Adverse event (AEs) were monitored by National Cancer Institution toxicity criteria. Results: 112 subjects were randomised: 60 men and 52 women at a mean age of 38 years. For the 89 patients who had landmark-matched polyp counts available at baseline and 6 months, the mean % change in adenoma count over the 6 months of trial was −13.0% for CXB+DFMO and −1.0% for CXB (p=0.69). Mean % change in adenoma burden was −40% (CXB+DFMO) vs −27% (CXB) (p=0.13). Video-based global polyp change was −0.80 for CXB+DFMO vs −0.33 for CXB (p=0.03). Fatigue was the only significant AE, worse on the CXB arm (p=0.02). Conclusions: CXB combined with DFMO yielded moderate synergy according to a video-based global assessment. No significant difference in adenoma count, the primary endpoint, was seen between the two study arms. No evidence of DFMO-related ototoxicity was seen. There were no adverse cardiovascular outcomes in either trial arm and no significant increase in AEs in the CXB+DFMO arm of the trial. Differences in outcomes between primary and secondary endpoints may relate to sensitivity of the endpoint measures themselves. Trial registration number: ClinicalTrials.gov number N01-CN95040.